A review of signal pathway induced by virulent protein CagA of Helicobacter pylori - Wang, Haiqiang; Zhao, Mei; Shi, Fan; Zheng, Shudan; Xiong, Li; Zheng, Lihong (Frontiers in Cellular and Infection Microbiology, 2023)
Gastric cancer (GC), a common and high-mortality disease, still occupies an important position in current cancer research, and Helicobacter pylori (H. pylori) infection as its important risk factor has been a hot and challenging research area. Among the numerous pathogenic factors of H. pylori, the virulence protein CagA has been widely studied as the only bacterial-derived oncoprotein. It was found that CagA entering into gastric epithelial cells (GECs) can induce the dysregulation of multiple cellular pathways such as MAPK signaling pathway, PI3K/Akt signaling pathway, NF-κB signaling pathway, Wnt/β-catenin signaling pathway, JAK-STAT signaling pathway, Hippo signaling pathway through phosphorylation and non-phosphorylation. These disordered pathways cause pathological changes in morphology, adhesion, polarity, proliferation, movement, and other processes of GECs, which eventually promotes the occurrence of GC. With the deepening of H. pylori-related research, the research on CagA-induced abnormal signaling pathway has been updated and deepened to some extent, so the key signaling pathways activated by CagA are used as the main stem to sort out the pathogenesis of CagA in this paper, aiming to provide new strategies for the H. pylori infection and treatment of GC in the future.